e-Scode (electronic shelf code) - Md Radzi, Mohd Abdul Hafiz; Somi, Nur Amirah; Hasnan, Filzah Hanis; Ismikhairul, Nur Elisya (Universiti Teknologi MARA, Kedah, 2019)
Current library shelving uses QR code provided by the library as level security for the student to put their bag and other properties in one place without any worries. Therefore, the QR code will be given to the student at the beginning of the semester by e-mail. For the first semester student, they will get the QR code once they had created their student portal account. Meanwhile, for other semester student, they just need to renew to show the status of the student whether they are active students or not to continue using this service. This concept of renewing is aimed not to burden the students financial. This is because to use the shelf, they just need to scan on the right corner of the shelf to access and open it to keep their bags and their properties. Besides, the advantage of the QR code is they do not need to bring any physical things to use the shelf because all students confirm will bring their smartphone. Also, the usage of QR code will not easily lose and damaged compared to the usage of a traditional card. The purposes of the QR code are easy to keep the stuff, organized, more secure and systematic. To conclude, every student must apply this service because to make it their life more systematic.